SAXS/WAXS Investigation of Amyloid-β(16-22) Peptide Nanotubes - Narayanan, Theyencheri; Rüter, Axel; Olsson, Ulf (Frontiers in Bioengineering and Biotechnology, 2021)
This brief report presents an X-ray scattering investigation of self-assembled nanotubes formed by short peptides. X-ray scattering methods enable multiscale structural elucidation of these nanotubes in solution under the same conditions involved in the self-assembly process. In particular, the dimensions of nanotubes and the crystalline organization within their walls can be determined accurately. This is illustrated in the case of amyloid-$β$(16-22) peptide nanotubes.